Numerical and experimental study on the influence of material characteristics on the levitation performance of squeeze-film air bearing. (October 2018) - Shi, Minghui; An, Lin; Feng, Kai; Guo, Zhiyang; Liu, Wanhui
Abstract: This research investigated the effects of material characteristics on the load-carrying capacity of squeeze-film air bearings (SFABs). Bearings with the same size and structure but are made of different materials, namely, aluminum (AL 2024), brass (CuSn35), and spring steel (60Si2Mn), were manufactured and tested. A theoretical analysis model was established to investigate the levitation performance of SFABs by coupling the near-field acoustic levitation (NFAL) and flexure pivot-tilting pad models. A test apparatus with the facility of measuring the floating performance of a shaft was designed and fabricated. Studies have shown that material characteristics are extremely important for the levitation performance of SFABs, and aluminium (AL 2024) was identified as the most suitable materials among the three materials. Highlights: Three novel squeeze film air bearings (SFABs) made of different materials are manufactured and tested. A theoretical model which considers near-field acoustic levitation (NFAL) and flexure pivot-tilting pad models is proposed. Resonant frequencies and corresponding modes of the test SFABs were obtained by finite element analysis and experiment. The bearing structure parameters effects on levitation performance is investigated. Experiments were conducted to investigated the floating performance of a shaft supported on SFABs with different materials.